The Roles of Memorable Tourism Experiences in Understanding Revisit - Wakjira, Gada Gizachew (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
The world economy was shifting to new ones. The tourism industry is also changing with new concepts. The local visitors’ behavior has also changed from traditional ones to new ones in last few decades. Currently, Myanmar tourism industry mainly focused on exploring the experience economy for travelers. Thus, this study aims to examine the effect of memorable tourism experiences on revisit intention. The purposive sampling method was used in this study. The target respondents were travelers who had experience hiking. Although, the questionnaire was distributed to 150 people, only 140 of them were valid for this study. The descriptive analysis and multiple regression methods used to test the proposed hypotheses. This study found that refreshment, involvement, meaningfulness, and surprise experiences have a positively significant effect on revisit intention.